KAJIAN AJARAN ETIKA DALAM KITAB SARASAMUCCAYA - I Wayan Gara (Jurnal Widya Sastra Pendidikan Agama Hindu, 2020)
Ethics is part of the three teachings of the basic framework of Hinduism contained in the Sarasamuccaya book, the Sarasamuccaya book is a guideline for good behavior in human life, which contains religious and ethical teachings. The problem raised in this research is regarding the ethical aspects (teachings) in the Sarasamuccaya book, the purpose of this study is to examine the ethical aspects of the Sarasamuccaya book, while the benefits are expected to increase the insight and morals or ethics of Hindus as implied in the Sarasamuccaya book. The discussion of this research problem rests on three theories: religious theory, structural functional theory, and symbol theory, ethical theory, and interpretation / hermeneutic theory. The research methods consist of: (1) data collection methods, (2) documentation methods, (3) data analysis methods, the results of the assessment in this paper include: (1) Catur Purusa Artha, which consists of: dharma, artha, kama, and moksa; (2) Tri Kaya Parisudha, which consists of: kayika parisudha, wacika parisudha, and manacika parisudha; (3) respect for others and parents, and (4) the teachings of dasa yama, which consists of: Anrsangsya, ksama, satya, ahingsa, dama, arjawa, priti, prasada, madhurya, and mardana.